The New Creation of Shanxi Gu Modern Dance - Lu, Wang; Roongruang , Panya; Thanawat, Arthorn (Journal of Roi Kaensarn Academi, 2024)
This article takes the Shanxi Gu dance as the main content, focusing on analyzing the historical origin, development, and inheritance of the Shanxi Gu dance. Based on this, it deeply explores the performance forms, dance techniques, and expression techniques of original the Shanxi Gu dance, as well as its cultural connotations and social significance expressed under different historical conditions. On the premise of integrating modern perspectives, we have made a new creation of the original ecological the Shanxi Gu dance and explored the problems encountered in the inheritance and innovation of the Shanxi Gu dance, in order to provide some reference for related research.